Development of a novel combined energy plant for multigeneration with hydrogen and ammonia production - Yuksel, Yunus Emre; Ozturk, Murat; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
In order to meet the energy and fuel needs of societies in a sustainable way and hence preserve the environment, there is a strong need for clean, efficient and low-emission energy systems. In this regard, it is aimed to generate cleaner energy outputs, such as electricity, hydrogen and ammonia as well as some additional useful commodities by utilizing both methane gas and the waste heat of an integrated unit to the whole system. In this paper, a novel multi-generation plant is proposed to generate power, hydrogen and ammonia as a chemical fuel, drying, freshwater, heating, and cooling. For this reason, the Brayton cycle as prime unit using methane gas is integrated into the s-CO2 power cycle, organic Rankine cycle, PEM electrolyzer, freshwater production unit, cooling cycle and dryer unit. In order then to evaluate the designed integrated multigeneration system, thermodynamic analyses and parametric studies are performed, revealing that the energy and exergy efficiencies of the whole plant are found to be 69.08% and 65.42%. In addition, ammonia and hydrogen production rates have been found to be 0.2462 kg/s and 0.0631 kg/s for the methane fuel mass flow rate of 1.51 kg/s. Also, the effects of the reference temperature, pinch point temperature of superheater, combustion chamber temperature, gas turbine input pressure, and mass flow rate of fuel on numerous parameters and performance of the plant are investigated. (c) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved. Superscript/Subscript Available
Keywords: Hydrogen; Ammonia; Power generation; Efficiency; Exergy; Multigeneration; Sustainability; SYSTEM; POWER; WATER; CYCLE; Chemistry; Electrochemistry; Energy & Fuels